Cloth Crafts of India Cotton and Silk, Trade and History - Mueller, Peggy; Turkovich, Marilyn; Associations in Multicultural and International Education, Chicago, IL. ([S.l.] : Distributed by ERIC Clearinghouse, 1987)
This resource suggests that to study India without experiencing the life of the people as represented through their folk craft traditions would be a hollow venture. History and geography are conveyed in the symbols and figures that decorate Indian crafts. Basic beliefs, ancient symbols, and religious traditions are conveyed in recurring visual images. The focus of this instructional guide is on the traditional fabric arts, including weaving, embroidery, applique, dyed, and printed materials. Background information, discussion guides, worksheets, and activities are given on topics which include: "Cotton and Trade"; "Fiber Investigation"; "East India Company and Gandhi"; "The Silk Tradition"; and "A Weaver's Village: Nuapatna." A timeline and bibliography are provided. (MM)
Availability: World Eagle, IBA, Inc., 111 King St., Littleton, MA 01460-1527 ($7.95).
Students.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Art Activities; Design Crafts; Elementary Secondary Education; Folk Culture; Foreign Countries; Geography; Handicrafts; Instructional Materials; Multicultural Education; Non Western Civilization; Social Studies; Symbolism; Visual Arts; Cotton -- India -- Silk; Folk Art -- Textiles -- Weaving; Guides, Classroom -- Learner